The Factors Affecting on Managing Sensitive Data in Cloud Computing - Haifaa Jassim Muhasin; Rodziah Atan; Marzanah A. Jabar; Salfarina Abdullah (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Cloud computing represents the most important shift in computing and information technology (IT). However, security and privacy remain the main obstacles to its widespread adoption. In this research we will review the security and privacy challenges that affect critical data in cloud computing and identify solutions that are used to address these challenges. Some questions that need answers are: (a) User access management, (b) Protect privacy of sensitive data, (c) Identity anonymity to protect the Identity of user and data file. To answer these questions, a systematic literature review was conducted and structured interview with several security experts working on cloud computing security to investigate the main objectives of proposed framework, a pilot study by using a structured questionnaire was conducted. Framework using multilevel to enhance management information system on sensitive data in cloud environment.